Structural Behavior of Unbalanced Section self-compacting reinforced concrete axially Loaded columns - Najim Abbas, Aamer; Muhammed, Nura Jasim (International Journal of Engineering and Technology, 2018)
Eight (120 mm) square and (1 m) long reinforced concrete columns were tested under axial load to large inelastic deformations. The main purpose of this research was to investigate the behavior of column sections confined by rectilinear ties. Major variables considered in this program included: (1) Distribution of longitudinal and lateral steel, including unbalanced section due to the asymmetric distribution of reinforcing steel bars (2) type of concrete; normal concrete and self-compacting concrete. Finite element model was performed to validate the experimental results of this investigation. Test results indicate that a asymmetric distribution longitudinal bars results in desired performance of columns. Unsupported longitudinal bars and its number effective only at large deformations and result in rapid deterioration of column behavior at a later stage. There is 8.75% and 35.65% decrease in ultimate capacity under the control column, asymmetric distribution of reinforcing steel bars appears a more brittle while symmetric bars yields more elastic than brittle, it adds safety when failure happens.Â Â Â